Development of the sexually transmitted infection service evaluation tool: Use of Delphi approach - Bansari L Chawada; Jayendrakumar K Kosambiya; Vipul P Chaudhari; Kristen J Wells (Wolters Kluwer Medknow Publications, 2018)
Background: With the wide variation in sexually transmitted infection (STI) services, it is a challenge to devise strategies for ensuring effective service delivery. The objectives of this study were to develop a standard tool for STI services evaluation and use the Delphi method to derive a weighted factor for each parameter of the tool. Methods: A review of existing guidelines for quality care STI services were conducted, and parameters were selected to form the content of the measurement tool. Delphi technique was used to derive weighted factor for each STI service delivery parameter by using the Likert scale of 0-7. A heterogeneous group of 18 anonymous experts was invited to rate the parameters. All the responses were collected online. Cronbach's alpha level ≥0.8 was selected to define consensus the experts. Results: The STI service evaluation tool (SSET) was created including ten parameters to evaluate the performance of clinic with the help of standard National guidelines. The SSET was standardized by deriving weighted factor for each evaluation parameter. Three rounds of Delphi were required to achieve consistency. Response rates for each Delphi round were 77.78%, 100%, and 78.57%, respectively. Each parameter, such as workforce, materials, consumables, consultation, counseling, coverage, referral, records, information education and communication, and supervision, was assigned weighted factor derived by converting the final score into the total standard score of 100. Conclusion: The Delphi method represents a novel approach to develop standardized tools to evaluate the performance of service delivery.